Intragranular flux pinning mechanism in Fe and Ni doped YBa2Cu3O7-δ - Wördenweber R.; Heinemann K.; Sastry G.V.S.; Freyhardt H.C. (My University, 2025)
The intragranular pinning properties of polycrystalline YBa2(Cu1-xMx)3O7-gd with M=Fe,Ni and x=0.05 are determined by magnetization measurements. The volume pinning force is interpreted in terms of flux-line shear, i.e. Fp is related to the on-set of dissipative flux-flow within weakly pinning channels in the superconductor. A quantitative analysis of our data yields a channel width comparable to the flux-line spacing ao. This indicates that single rows of flux-lines seem to move once the Lorentz force exceeds the flow stress of the flux-line lattice. Experimental evidence is given that the pinning of the flux lines outside the channels cannot be caused by twin boundaries. © 1989.